ANALISIS PREFERENSI RUMAH TANGGA TERHADAP PRODUK JAMU SELAMA MASA PANDEMI COVID-19 DI RUMAH TANGGA, KELURAHAN BAKTIJAYA KECAMATAN SUKMAJAYA DEPOK - Asma Hasanah; Trisna Insan Noor (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Corona Virus Disease 2019 (Covid-19) or commonly referred to as the Corona Virus is a disease outbreak that is currently a concern all over the world, one of which is Indonesia. Covid-19 is a disease that comes from a virus, when the virus enters the body it will be detected by the body's immune system. If the body's immune system is strong enough, the virus can be resisted by the body's antibodies by itself. Therefore, the right way while waiting for an antiviral is to increase the body's immunity so that the possibility of contracting Covid-19 infection is smaller. Jamu is a traditional medicine that is believed to increase the body's immunity. Jamu is part of traditional medicine that has been used by Indonesians for generations as a treatment. The purpose of this study was to analyze the category of attributes that became household preferences for herbal products during the Covid-19 Pandemic in RT 09 and 10 (Keluruhan Baktijaya, Kecamatan Sukmajaya RW 021) Depok City. The analytical methods used in this research are Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). Based on the results of IPA, it was obtained that household preferences for herbal products showed that the most important attribute categories in each attribute were herbal medicine in liquid form, the properties of herbal medicine to maintain health, the price of jamu <5,000 and 5,000 - 10,000 rupiah, and the bitter taste of herbal medicine. Based on the CSI results, the majority of household were satisfied with the performance of the attributes of the medicinal products consumed.